Clinton and Japan the impact of revisionism on US trade policy - Uriu, Robert M., 1959- (Oxford : Oxford University Press, 2009)
This book chronicles how a controversial set of policy assumptions about the Japanese economy, known as revisionism rose to become the basis of the trade policy approach of the Clinton administration, and details how Japan refused to accept US trade solutions and fought to discredit revisionism.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Protectionism -- Japan; Foreign trade regulation -- United States; Foreign trade regulation -- Japan; United States -- Commerce -- Japan; Japan -- Commerce -- United States; United States -- Politics and government -- 1993-2001.; Japan -- Politics and government -- 1989-